Evaluation of Stable, and Adaptable Wheat Genotypes under Late Sown (Heat Stress) and Drought under Late Sown (Heat-Drought) Conditions - Nyaupane, Shivalal; Bhandari, Radhakrishna; Poudel, Mukti Ram (Fundamental and Applied Agriculture, 2024)
Heat stress and drought are the major problems for wheat production. Heat stress and drought causes a significant yield reduction of wheat in Nepal. To evaluate the stability, and adaptability of wheat genotypes, a field experiment was conducted using 20 elite wheat genotypes at the Institute of Agriculture and Animal Science (IAAS), Paklihawa Campus, Nepal in an alpha lattice design with two replication. AMMI model revealed that environment had a significant effect on grain yield of wheat and explained 55.22% of the total variation in grain yield. Which-Won-Where model showed that NL 1404 and NL 1386 were the most stable genotypes across late sown and drought under late sown conditions whereas, NL 1368 and Bhirkuti were specifically adapted genotypes under late sown and drought under late sown conditions, respectively. Thus, these genotypes can be used for yield improvement wheat under combined heat-drought conditions.